Students’ Responses to Multimodal Texts in Learning Reading Course - Fitriani, Siti Amalia; Kurniawati, Nia; Aminuddin, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2024)
Multimodal text is one of the media in learning English reading courses commonly used in this advanced technology era, since multimodal texts combine a variety of modes, such as visual and auditory. Moreover, multimodal texts have several positive effects on improving students’ reading ability, especially reading comprehension. However, reading aloud without comprehending the text's meaning still probably occurs among EFL students in Indonesia. Thus, this research aims to explore the students’ responses to multimodal texts in learning reading courses and the contribution of multimodal texts to the student’s reading comprehension. This research employed a qualitative approach with a case study design. A questionnaire and a test were applied to collect the data. Fourteen ninth-grade students of MTs Miftahul Huda were chosen as participants. The result shows that most students responded positively to multimodal texts in the learning reading course. Multimodal texts may make the students enjoy, be interested, and be motivated in the learning process and help them understand the information in the text. It may also have a good contribution to the students’ reading comprehension. Nevertheless, the role of the teacher is critical in the learning process. Teachers can use a variety of multimodal texts in teaching reading course to take the advantage of multimodal texts in learning reading course